Mosaic or Melting Pot? Race and Juror Decision Making in Canada and the United States - Maeder, Evelyn M. (Journal of interpersonal violence, 2022)
Although Canada and the United States both demonstrate significant overrepresentation of racialized groups in prisons, the overrepresented groups vary by country, potentially signifying results of the countries’ different (though similarly problematic) histories of racial inequality. The present study investigated this issue within a jury context by assessing the influence of defendant race on Canadian and American participants’ verdicts in an assault trial. We also examined mock jurors’ attributions of the defendant’s behavior and their perceptions of the cultural criminal stereotype for each racial group. Canadian and American participants (N = 198) read a trial transcript in which the defendant’s race (i.e., Black, White, or Aboriginal Canadian/Native American) was manipulated, and then completed measures of attributions and stereotypes. Results demonstrated that although verdicts did not significantly differ as a function of defendant race or country, stability and control attributions did vary between Canadian and American participants, as did racial stereotypes. In addition, defendant race affected internal versus external attributions, regardless of country. These findings suggest that race may play a role in jurors’ perceptions of defendants, but that in some ways, this varies by country, potentially accounting for some of the differences found between existing Canadian and American jury studies.